Natural radioactivity of Pamir mineral waters (Tajikistan) - Chelnokov George; Lavrushin Vasilii; Kharitonova Natalia; Pavlov Andrey (E3S Web of Conferences)
In the present article, radon and uranium concentrations of nineteen occurrences of mineral waters of Pamir are considered in conjunction with geological conditions and physical and chemical characteristics. The results of uranium and radon determinations were compared with the data of chemical and isotopic analyses of waters and gases. Obtained data indicate that thermal water of Pamir are weakly radioactive (222Rn < 130 Bq/l) and contain uranium concentrations not exceeding the norms for drinking water (U<15 μg/l). The altitude of the mineral springs above sea level, as well as the uranium and δ18O content of the waters, were shown to be connected with the 222Rn activity concentrations. This agrees well with previous isotopic data showing that the waters and gases of the Pamirs have a weak connection with the deep horizons of the Earth's crust. Therefore, the primary source of radon in the water circulation zone is rock minerals; radon transfer by deep gases in the Pamir structures is insignificant. Although low levels of 222Rn in Pamir's mineral water are unsuitable for balneological uses, natural items with similar characteristics can be included to forecast earthquakes and observe the current state of the geological environment.